The incidence, aetiology, and coagulation management of massive postpartum haemorrhage: a two-year national prospective cohort study. (August 2021) - Bell, S.F.; Collis, R.E.; Bailey, C.; James, K.; John, M.; Kelly, K.; Kitchen, T.; Scarr, C.; Macgillivray, E.; Collins, P.W.
Highlights: Prospective study of massive postpartum haemorrhage. The rate in Wales (2017–2018) was 5.7 per 1000 maternities. Red blood cells were received by 80.6% and coagulation products by 22.9%. Point-of-care assays were recorded in 70.2% and increased over time. Hypofibrinogenaemia was the most frequent coagulation deficit, occurring in 17.1%. Abstract: Introduction: Between 2017 and 2018 a national quality improvement initiative was introduced incorporating point-of-care viscoelastic haemostatic assays (VHA) to guide blood product transfusion. Laboratory coagulation profiles, use and results of VHA, and administration of blood products were investigated. Methods: A two-year prospective cohort study of maternal outcomes of women experiencing massive postpartum haemorrhage (PPH) >1000 mL in Wales. In this study, cases of massive PPH (≥2500 mL and/or ≥5 units red blood cell (RBC) transfusion) were identified. Results: Massive PPH occurred in 349 of 60 914 maternities (rate 5.7 per 1000). There were no deaths from PPH. Intensive care unit admission and/or hysterectomy occurred in 34/311 (10.9%) and 16/347 (4.6%), respectively. The leading cause of massive PPH was genital tract trauma (107/349, 30.6%). Two hundred and seventy-nine (80.6%) required RBC transfusion and 79/345 (22.9%) received at least one blood coagulation product. Results of VHA were recorded in 245/349 (70.2%), with 44/98 (44.9%) women tested in the first six months vs 63/77 (81.8%) in the final six months. Hypofibrinogenaemia (Clauss fibrinogen <2 g/L or FIBTEM A5 <12 mm) was observed in 56/328 (17.1%) of women, thrombocytopaenia (count <75 × 10 9 /L) in 17/334 (5.1%) and either PT or aPTT >1.5×reference range in 10/293 (3.4%). Conclusion: In Wales, the use of VHA in cases of massive PPH increased over time, enabling clinicians to adopt a targeted, patient-specific approach to blood product administration, with only 22.9% of women receiving blood coagulation products and 17.1% having a documented clotting abnormality.